Koencim Q 10 - Rus, Primož (Zdravstveno varstvo, 2008)
Coenzyme Q 10 (CoQ), also known as ubiquinone, is a vitamin-like substance. It is important in adenosine triphosphate (ATP) synthesis in mitochondria and t is an effective antioxidant. The deficiency of CoQ is due to insuffcient dietary intake of CoQ, impairment in its biosynthesis, or excessive utilization of CoQ by the body. The dominant sources of CoQ in man are biosynthesis and dietary intake. The paper describes the role of CoQ in the prevention and treatment of cardiovascular diseases, migraine, mitochondrial and other diseases. Drug interactions, dosage and side effects observed duringCoQ treatment are described.
Keywords: antioksidanti; antioxidant; koencim Q10; stranski učinki; therapy; ubikinon; zdravljenje